The writer's handbook for sociology - Young, Dona J (Routledge, 2018)
The Writer's Handbook for Sociology gives students the tools that they need to develop evidence-based writing skills and format academic papers in American Psychological Association (APA) and American Sociological Association (ASA) style. This book helps learners develop a reader-friendly writing style incorporating active voice, parallel structure, and conciseness. In addition, grammar and mechanics are presented in a systematic way to facilitate learning, helping students fill learning gaps.